Tactical and strategic driving behaviour in older drivers: The importance of readiness to change. (June 2020) - Dykstra, Christopher; Davis, Jessica. J.; Conlon, Elizabeth G.
Highlights: Readiness promoted tactical behaviour for older drivers without health difficulties. Readiness promoted tactical behaviour for young-old drivers with health difficulties. Readiness promoted strategic self-regulation more for women and with older age. Multidimensional driving self-regulation includes strategic and tactical behaviour. Abstract: The aim of this study was to explore the way in which reports of strategic and tactical driving self-regulation are influenced by readiness to change driving behaviour in older men and women, either reporting or not reporting modification of driving behaviour for health-related reasons, and/or increased driving difficulty. Current Australian drivers aged over 60 years (N = 258) responded to a self-report questionnaire. Hierarchical regression analyses indicated increased use of tactical behaviours were associated with greater driving difficulty, more readiness to change and male gender (R 2  = 23.2%) . These effects were moderated by a significant association between readiness to change, driving modifications for health reasons and age (R 2 chg  = 2.9%). Greater readiness to change was associated with increased use of tactical behaviours for older drivers who did not modify driving for health reasons, independent of ageIndependent of age. This association was also found for younger old drivers with health difficulties, but not for older old drivers with health difficulties. Hierarchical regression indicated that greater readiness to change, increased driving difficulty, female gender and modification of driving for health reasons were associated with reports of increased strategic self-regulation (R 2  = 50.8%). These effects were moderated by readiness to change and age, and readiness to change and gender (R 2 chg  = 2.1%). The association between readiness to change and strategic self-regulation was stronger for women than men, and the strength of this association became substantially stronger with increasing age. It was concluded that readiness to change driving behaviour may promote different forms of driving self-regulation for different individuals, and that older drivers may use the different forms of driving self-regulation independently of one another.